Strengthening Abadi Tani Farmers in Fish Feed Production Training Using Peunia Village Local Materials, West Aceh - Friyuanita Lubis; Oviana Lisa; Yulia Windi Tanjung; Siti Aminah; Deski Priatama Wijaya (Mitra Akademia Indonesia, 2026)
Fish farming is a vital economic resource for the people of West Aceh, including the Abadi Tani Farmers Group in Peunia Village. However, heavy reliance on artificial feed is a major obstacle, as feed costs account for approximately 60% of total production. Fluctuating feed prices leave farmers vulnerable to losses and even lead to the abandonment of farming. Therefore, alternative feeds are needed to support the sustainability of freshwater fish farming. The Abadi Tani Farmers Group still has limited experience and facilities for independent pellet production. Training on making pellets from local water hyacinth provides a solution for producing low-cost, environmentally friendly feed and can reduce fish farming production costs. The results showed that water hyacinth, a local ingredient abundant in the waters of Peunia Village, is used as an ingredient in artificial feed with the addition of bran, fish meal, cassava flour, a strengthening agent, and vegetable oil. This mixture produces approximately 3 kg of feed, which is packaged in 500-gram plastic bags. Prior to the training, respondents' understanding of water hyacinth-based feed production was still low, with only 20% understanding the process. After the training, respondents' understanding increased significantly to 70%, while the number of respondents in the